Profil Kandungan Kimia dan Potensi Senyawa Aktif Limbah FABA untuk Pengembangan Pupuk Berkelanjutan - Wiwin Rewini Kunusa; Suleman Duengo; Julhim S. Tangio; Erni Mohamad; Nurul Fadilla Harun; Humairah Amatullah Duengo; Nuur Arif Syaifudin (Jambura Journal of Chemistry, 2026)
Fly ash and bottom ash (FABA) generated from coal combustion in steam power plants have the potential to cause environmental contamination; however, their mineral content enables their reutilization as raw materials for inorganic fertilizers. This study aimed to evaluate the major metal element content in FABA-based fertilizer produced from the Anggrek Steam Power Plant, North Gorontalo Regency, in order to assess its potential as a nutrient source. Ca and Mg were analyzed using titration methods, while Al, Fe, P, and K were determined by UV–Vis spectrophotometry with good calibration curve linearity (r 0.97). The results showed that the K content in fertilizer samples 1 and 2 was 0.0189% and 0.0140%, respectively. Ca concentrations ranged from 16.8–21.6 mg/L and Mg from 7.29–10.21 mg/L. Al was detected within the range of 3.68–4.44 ppm, while Fe and P were identified in measurable amounts. The presence of Ca, Mg, and K as macronutrients indicates that FABA waste has potential as a raw material for inorganic fertilizer, while also supporting sustainable industrial waste management practices.